Orofacial operant behaviors and electrophysiological properties of trigeminal ganglion neurons following masseter muscle inflammation in rats. (16th February 2019) - Viatchenko-Karpinski, Viacheslav; Erol, Ferhat; Ling, Jennifer; Reed, William; Gu, Jianguo G.
Highlights: Orofacial muscle pain is a significant clinical problem because it affects eating, speaking, and other orofacial functions in patients. However, mechanisms underlying orofacial muscle pain are not fully understood. In the present study we induced orofacial muscle pain by injecting Complete Freund's Adjuvant (CFA) into masseter muscle of rats and assessed pain by the orofacial operant test. We also retrogradely labeled trigeminal ganglion neurons that innervated masseter muscles, and performed in situ patch-clamp recordings from these neurons. A main finding is that orofacial muscle pain in our CFA model is accompanied by significant changes of electrophysiological properties and background K + currents in trigeminal ganglion neurons that innervate masseter muscles. Abstract: Orofacial muscle pain is a significant clinical problem because it affects eating, speaking, and other orofacial functions in patients. However, mechanisms underlying orofacial muscle pain are not fully understood. In the present study we induced orofacial muscle pain by injecting Complete Freund's Adjuvant (CFA) into masseter muscle of rats and assessed pain by the orofacial operant test. In comparison with the control group, CFA-injected animals (CFA group) showed decreases in operant behaviors, suggesting the presence of orofacial pain. Trigeminal ganglion (TG) neurons innervating masseter muscles were retrograde-labeled with DiI and their electrophysiological properties studied using patch-clamp recordings. About 20% of DiI-labeled TG neurons showed spontaneous action potentials (APs) in the CFA group but none in the control group. AP rheobase levels were significantly lower in DiI-labeled TG neurons of the CFA group than in the control group. Membrane input resistance of DiI-labeled TG neurons was significantly higher in the CFA group than in the control group. Several other membrane parameters were also different between DiI-labeled TG neurons of the CFA and control groups. Voltage-dependent currents were examined and the most significant changes following CFA were background K + currents, which showed significantly smaller in DiI-labeled TG neurons of CFA group compared to the control group. Collectively, orofacial muscle pain in CFA model is accompanied with changes of electrophysiological properties and background K + currents in TG neurons that innervate masseter muscles.